La communication humaine en communication! - Johanne Saint-Charles; Pierre Mongeau (Communiquer)
By telling the story of the development of the field of human communication at Université du Québec à Montréal (UQAM), we show how the institutionalization of communication studies depends upon the meeting of scholarly programs in both human communication and media communication. We then propose a definition of the object of study of human communication and present contributions to the emergence of this new field made by professors. This allows us to highlight avenues for the development of research and training in human communication.